Breaking the Chains of Job-Hopping: The Interplay of Job Involvement, Satisfaction, and Affective Commitment Among Millennials - Tantri Ratna Dewi; Dian Ekowati (Jurnal Manajemen Teori dan Terapan)
Objective: The purpose of this paper is to examine the influence of job involvement, job satisfaction, and affective commitment on job-hopping behavior, as well as the moderating effect of alternative employment opportunities on millennial employees.